Assessment of bacterial and structural dynamics in aerobic granular biofilms - Weissbrodt, David G.; Neu, Thomas R.; Kuhlicke, Ute; Rappaz, Yoan; Holliger, Christof (Frontiers in Microbiology, 2013)
Aerobic granular sludge is based on self-granulated flocs forming mobile biofilms with a gel-like consistence. Bacterial and structural dynamics from flocs to granules were followed in anaerobic-aerobic sequencing batch reactors fed with synthetic wastewater, namely a bubble column (BC-SBR) operated under wash-out conditions for fast granulation, and two stirred-tank enrichments of Accumulibacter (PAO-SBR) and Competibacter (GAO-SBR) operated at steady-state. In the BC-SBR, granules formed within two weeks by swelling of Zoogloea colonies around flocs, developing subsequently smooth zoogloeal biofilms. However, Zoogloea predominance (37-79%) led to deteriorated nutrient removal during the first months of reactor operation. Upon maturation, improved nitrification (80-100%), nitrogen removal (43-83%), and high but unstable dephosphatation (75-100%) were obtained. Proliferation of dense clusters of nitrifiers, Accumulibacter, and Competibacter from granule cores outwards resulted in heterogeneous bioaggregates, inside which only low abundance Zoogloea (<5%) were detected in biofilm interstices. The presence of different extracellular glycoconjugates detected by fluorescence lectin-binding analysis showed the complex nature of the intracellular matrix of these granules. In the PAO-SBR, granulation occurred within two months with abundant and active Accumulibacter populations (56±10%) that were selected under full anaerobic uptake of volatile fatty acids and that aggregated as dense clusters within heterogeneous granules. Flocs self-granulated in the GAO-SBR after 480 days during a period of over-aeration caused by biofilm growth on the oxygen sensor. Granules were dominated by heterogeneous clusters of Competibacter (37±11%). Zoogloea were never abundant in biomass of both PAO- and GAO-SBRs. This study showed that Zoogloea, Accumulibacter, and Competibacter affiliates can form granules, and that the granulation mechanisms rely on the dominant population involved.